Khūm̄ư witthayāk̜̄on phūprasān kāns̄œmsāng khwāmkhemkhæng kh̜̄ong chumchon (Samnak B̜̄orihān Kānpokkhr̜̄ong Th̜̄ongthī, Krom Kanpokkhr̜̄ong, 1999)
Locality strength enhancement program of the Department of Local Administration of Thailand.